2008
DOI: 10.3802/jgo.2008.19.4.229
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of sonographic morphology indexing and serum CA-125 for preoperative differentiation of malignant from benign ovarian tumors in patients after operation with ovarian tumors

Abstract: Objective:To evaluate the value of sonographic morphology indexing (MI) system and serum CA-125 levels in the assessment of the malignancy risk in patients with ovarian tumors. Methods: From September 2000 to July 2006, 202 patients who underwent surgery for ovarian tumors were reviewed retrospectively. In all patients, the MI score and serum CA-125 level were measured preoperatively. The association of the final pathologic diagnosis with the MI score and serum CA-125 level were examined. Results: There were 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
7
2
Order By: Relevance
“…26 The accuracy of this morphology index has been validated both in the United States 27 and internationally. 28,29 In patients with indeterminate tumor morphology, serial morphology index evaluations may be useful. Elder et al, 23 for example, evaluated serial morphology in 50 ovarian malignancies, 272 benign ovarian tumors, and 947 unilocular ovarian cysts.…”
Section: Tumor Morphologymentioning
confidence: 99%
“…26 The accuracy of this morphology index has been validated both in the United States 27 and internationally. 28,29 In patients with indeterminate tumor morphology, serial morphology index evaluations may be useful. Elder et al, 23 for example, evaluated serial morphology in 50 ovarian malignancies, 272 benign ovarian tumors, and 947 unilocular ovarian cysts.…”
Section: Tumor Morphologymentioning
confidence: 99%
“…). In addition, previous studies have found that, due to the solid and mixed structures on 2‐D US imaging, the scores of teratomas were high, resulting in their misdiagnosis as malignant masses. In our research, as shown in Table , the score of the teratoma was 5; in the old SMS, in which the cut‐off value was 5, the teratoma would be misdiagnosed as a malignant tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 20 years, SMS has been developed, revised and continuously modified from Sassone et al ., to DePriest et al ., to Lerner et al ., to Ueland et al ., to Alcázar et al ., to Timmerman et al . and to Jeoung et al Of these, the Ueland scoring system, which used 5 points as a cut‐off value to differentiate malignant tumors from benign ones, is the most commonly applied in the clinical evaluation of pelvic or adnexal masses due to its simplicity and high accuracy . Therefore, in this study, we compared our scoring system with the Ueland system to evaluate the accuracy of our new SMS system.…”
Section: Discussionmentioning
confidence: 99%
“…There have also been attempts to simplify the IOTA algorithm [17,18], and IOTA has yet to be evaluated in the United States. Other morphology-based indices have been proposed and validated in the U.S. and abroad [19,20,21]. Moreover, much like longitudinal CA125 (ROCA), serial ultrasound offers improved diagnostic results over a single evaluation (Figure 1) [22,23].…”
Section: Presentmentioning
confidence: 99%